Great Jobs for Engineering Majors (Great Jobs Series) - Garnerner Geraldine (Mc Graw Hill Higher Education, 2008)
You've worked hard for that engineering degree. Now what? Sometimes the choice of careers can seem endless; the most difficult part of a job search is narrowing down your options.